176k views
19 votes
Consider the following function: f(x)=-3/4x+9

place the steps for finding f-1 (x) in the correct order

User Brogrammer
by
5.8k points

2 Answers

10 votes
  • Let y=f(x)


\\ \tt\hookrightarrow y=(-3)/(4)x+9


\\ \tt\hookrightarrow y-9=(-3x)/(4)


\\ \tt\hookrightarrow -3x=4y-36


\\ \tt\hookrightarrow x=(-4)/(3)y+12

Now


\\ \tt\hookrightarrow f^(-1)x=(-4)/(3)x+12

User Bhushan Bhangale
by
4.5k points
11 votes

Answer:


f^(-1)(x) = ( (4y - 36)/(-3) )

Explanation:

f(x)=-3/4x+9

let f(x) be y .......................to find inverse we have making x the subject.

y = -3/4x+9

y - 9 = -3/4 x

-3x = 4y - 36

x = (4y - 36)/-3

so,
f^(-1)(x) = ( (4y - 36)/(-3) )

User Dollar Friend
by
5.5k points